Gender inequality in economic crises - Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (Investigaciones Feministas (Feminist Research), 2012)
This article presents a historical analysis of the economic crises of the last hundred years from a feminist economics perspective, highlighting three historical patterns that can help to advance in a deeper understanding of the current crisis and, above all, to guarantee a way out of this crisis with more and not less equality. The first pattern is that crises result in an intensification of women’s work, especially the unpaid care work. The second one is that after economic crises male employment recovery is always previous to the female employment, which always ends even more precarious; and the third pattern is that crisis lead to setbacks in the advances made in gender equality in terms of regulation, equality policies and the rules of the game in general.